Role of Villagers in Building Community Resilience Through Disaster Risk Management: A Case Study of a Flood-Prone Village on the Banks of the Mekong River in Cambodia - Serey Sok (2018)
© 2011, Springer Science+Business Media B.V. Floods are a normal feature of the monsoon season around the Tonle Sap Great Lake and areas neighboring the Mekong River in Cambodia. In some years, floods are much more severe than others; in particular, when there is a combination of high discharge from upstream and a high run-off from rainfall within the area. Actions taken by villagers could help build resilience at household and community levels against these more serious floods and thus reduce the risks of disasters, loss of life, and costly damage. In a detailed study of impacts and responses to floods in Angkor Ang village in Prey Veng Province, we found evidence of major barriers to effective actions by villagers and other actors working at community and other levels. Building and maintaining resilience in flood-prone communities requires that attention be given to local capacity and knowledge, differences in wealth or poverty, gender relations, and local participation. Moreover, these factors need to be examined in various social processes before, during, and after major floods.